318 HEALTH CARE POST-KATRINA: RECOMMENDATIONS FOR MEDICATION DONATIONS TO POSTDISASTER CLINICS. Issue 1 (1st January 2007) - Howe, E.; Victor, D.; Price, E. G.
Abstract : Background: In the aftermath of Hurricane Katrina, numerous postdisaster clinics relied on charitable donations of supplies and medications. Some medications were donated in excess, whereas others were limited in availability. Prior studies of posthurricane health care in the United States do not consistently offer evidence-based recommendations for directing such donations. Therefore, our primary study objective is to describe specific chief complaints, final diagnoses, and medications prescribed at a post-Katrina clinic to better inform future medication donations in similar situations. Methods: We conducted a retrospective chart review of 465 patient visits from September 2, 2005, to October 22, 2005, at a post-Katrina clinic in New Orleans. This temporary clinic was open for 7 weeks to provide free urgent and primary care services in the central business district after the storm. Using logistic regression, we examined the relationship between patient characteristics, date of visit, type of chief complaint (injury, illness, medication refills), final diagnosis, and type of medication prescribed. Results: Among the 465 visits, 62% occurred during the fourth and fifth weeks; 6.9% were repeat visits; 62% visits were with male patients; and the average patient age was 44 years (14 SD). Among 342 patient visits involving illness-related chief complaints, 30% included ENT complaints, 21% dermatology related, and 13.5% cardiovascular. Patient age, gender, or date of visit did not affect the odds of presenting with an illness complaint. Among 124 visits for prescription refill requests, 57% were for cardiovascular medications (ACEI/beta-blockers/calcium-channel blockers/diuretics/nitrates/anticoagulants), and 40.3% endocrine medications (hypoglycemics/thyroid/lipid lowering). After adjusting for age, gender, and date of visit, encounters with older patients versus younger patients, women versus men and later visits versus earlier visits were more likely to involve medication refill requests (adjusted OR 1.04, 95% CI 1.0-1.1, adjusted OR 2.5 [1.6-3.9]), adjusted OR 1.2 [1.0-1.5], respectively). There were 49 visits for injury-related complaints. Among all 465 visits, 22% had infection-related final diagnosis, and antibiotics were prescribed for 16% of visits. Other common treatments included NSAIDs (15% visits), inhalers/cough suppressants (14%), and antihistamine/leukotriene inhibitor/nasal steroids (13%). Conclusions: The most useful classes of medication donations postdisaster include antihypertensives, hypoglycemics, thyroid and lipid-lowering agents, antibiotics, analgesics, respiratory, and antiallergy.